Gellan gum : fermentative production, downstream processing and applications - Bajaj, Ishwar B. (Array, 2007)
The microbial exopolysaccharides are water-soluble polymers secreted by microorganisms during fermentation. The biopolymer gellan gum is a relatively recent addition to the family of microbial polysaccharides that is gaining much importance in food, pharmaceutical and chemical industries due to its novel properties. It is commercially produced by C. P. Kelco in Japan and the USA. Further research and development in biopolymer technology is expected to expand its use. This article presents a critical review of the available information on the gellan gum synthesized by Sphingomonas paucimobilis with special emphasis on its fermentative production and downstream processing. Rheological behaviour of fermentation broth during fermentative production of gellan gum and problems associated with mass transfer have been addressed. Information on the biosynthetic pathway of gellan gum, enzymes and precursors involved in gellan gum production and application of metabolic engineering for enhancement of yield of gellan gum has been specified Characteristics of gellan gum with respect to its structure, physicochemical properties, rheology of its solutions and gel formation behaviour are discussed. An attempt has also been made to review the current and potential applications of gellan gum in food, pharmaceutical and other industries